2007
DOI: 10.1021/jp067075v
|View full text |Cite
|
Sign up to set email alerts
|

Folding of the 25 Residue Aβ(12−36) Peptide in TFE/Water:  Temperature-Dependent Transition from a Funneled Free-Energy Landscape to a Rugged One

Abstract: The free-energy landscape of the Alzheimer beta-amyloid peptide Abeta(12-36) in a 40% (v/v) 2,2,2-trifluoroethanol (TFE)/water solution was determined by using multicanonical molecular dynamics simulations. Simulations using this enhanced conformational sampling technique were initiated from a random unfolded polypeptide conformation. Our simulations reliably folded the peptide to the experimental NMR structure, which consists of two linked helices. The shape of the free energy landscape for folding was found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 50 publications
0
32
0
Order By: Relevance
“…The stabilization effect of fluorinated solvents has also been shown in other MD simulation studies of different peptides [95,[135][136][137] and proteins [138].…”
Section: Fluorinated Alcoholsmentioning
confidence: 54%
“…The stabilization effect of fluorinated solvents has also been shown in other MD simulation studies of different peptides [95,[135][136][137] and proteins [138].…”
Section: Fluorinated Alcoholsmentioning
confidence: 54%
“…Typically, the folding free energy landscape of peptides shows the characteristic features of a funneled landscape, either with a downhill surface toward the folded basin or with a more rugged surface with local minima populating the unfolded basin 36,39–41 (a typical example is given in Figure 5). The degree of roughness was shown to strongly depend on the temperature 39–41. Comparison of the folding landscapes at different temperatures revealed that a temperature‐dependent transition from a funneled free energy landscape (at higher T) to a rugged one (at lower T) occurs for the studied peptides.…”
Section: Applicationsmentioning
confidence: 90%
“…The McMD simulation of a 25-residue segment from the Alzheimer's β amyloid peptide (Aβ) in a TFE/water co-solvent showed that this peptide folds into the experimentally determined helical structure (Kamiya et al 2007), although it is disordered in water (Ikebe et al 2007a). The free-energy landscape was funnel-like above 325 K, where the funnel bottom corresponded to the experimental structure, and the landscape transitioned abruptly to a rugged one below 325 K. This work might have captured a general property of the temperature-induced structural transition exhibited by many peptides/proteins.…”
Section: All-atom Mcmd Simulations Of Various Systemsmentioning
confidence: 99%